Profitability and Resource Use Efficiency of Mustard Cultivation - Sampa, AY; Sarker, F; Rahman, MR; Begum, R (SAARC Journal of Agriculture, 2021)
Climatic condition is conducive to cultivate mustard in Bangladesh and there are ample opportunity to improve the present scenario of production, since the demand of oilseeds is high. But economic analysis of production of this crop remains unnoticed most of the time. For assessment of the profitability and resource use efficiency, a field level study was conducted with 100 mustard growers, who were selected purposively and interviewed with pre tested questionnaire from Manikganj district during the period May to August 2019. Applying the Cobb-Douglas production model the results suggested that farmers earned 18577.91 Tk ha-1 by producing 1683.75 kg ha-1 Mustard with the Benefit Cost Ratio (BCR) 1.28. Land preparation cost, seed, human labour, irrigation and fertilizer had a significant positive effect on the yield of Mustard while insecticides had negative insignificant effect. Farmers were inefficient in case of resource use. Mustard cultivation is profitable in Bangladesh and has the potentiality to minimize import cost of oilseeds. Mustard production can be increased further by ensuring adequate supply of labor at peak period with reasonable wage rate, incentive price of produce for farmers, sufficient drainage system after flood, collateral free and easy access to credit, crop insurance to mustard growers. SAARC J. Agri., 18(2): 195-206 (2020)